PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD MATERI EKOSISTEM MATA PELAJARAN IPAS KELAS V SD NEGERI 29 PONTIANAK KOTA - Ramadhita, Resti; Kartono; Prasodjo, Bayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this research was to develop flashcard learning media for ecosystems that met the eligibility criteria based on validity and readability tests by teachers and students. The research used the ADDIE model, a development method limited to the implementation stage. Quantitative data were obtained through expert assessments and teacher and student readability questionnaires, while qualitative data came from suggestions from validators and teachers. Data collection techniques included observation, interviews, and questionnaires, with instruments consisting of observation sheets, interview guides, validation sheets, and response questionnaires. The study subjects consisted of three teachers and six students in class V B of SDN 29 Pontianak City. The feasibility test results showed that the material aspect received a score of 98%, the media aspect 97%, and the language aspect 100%, all in the